2022
DOI: 10.1080/07853890.2022.2031272
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the deep immune profiling of B cell subsets between healthy adults and Sjögren’s syndrome

Abstract: Objectives Detailed analysis targeting B cell subgroups was considered crucial in monitoring autoimmune diseases and treatment responses. Thus, precisely describing the phenotypes of B cell differentiation and their variation in primary Sjögren’s syndrome (pSS) is particularly needed. Methods To characterize the proportions and absolute counts of B cell subsets, peripheral blood from 114 healthy adults of China (age range: 19–73 years) and 55 patients with pSS were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Consistent with previous studies, 55 , 56 we found that the proportion of VPREB3 + memory B cells is decreased in PBMCs and increased in the SG of patients with pSS, potentially due to enhanced migration to target organs. The percentage of naive B cells is reportedly higher in PBMCs of patients with pSS than in healthy individuals, 57 , 58 which is in line with our results showing an expanded IGHD + naive B cell subpopulation among PBMCs of patients with pSS. We also observed that BANK1 + and CD83 + B cell subsets increased in the SG of patients with pSS, indicating local expansion of effector B cells.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, 55 , 56 we found that the proportion of VPREB3 + memory B cells is decreased in PBMCs and increased in the SG of patients with pSS, potentially due to enhanced migration to target organs. The percentage of naive B cells is reportedly higher in PBMCs of patients with pSS than in healthy individuals, 57 , 58 which is in line with our results showing an expanded IGHD + naive B cell subpopulation among PBMCs of patients with pSS. We also observed that BANK1 + and CD83 + B cell subsets increased in the SG of patients with pSS, indicating local expansion of effector B cells.…”
Section: Discussionsupporting
confidence: 91%
“…2 c). Previous studies have shown that CD24, CD27 and IgD can be used to illustrate the maturation process of B cells [ 12 , 13 ]. Consistent with previous studies, our results revealed that IGHD and CD24 were mainly expressed on naïve B cells and that CD27 was mainly expressed on CD27 + memory B cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a negative correlation between autoantibody concentrations and frequency of unswitched-memory B cells suggests that this subset may be protective against autoimmunity. Thus, lower percentages of unswitched-memory B cells are seen in systemic lupus erythematosus (SLE) and Sjögren’s syndrome (SS) patients, in whom higher concentrations of autoreactive antibodies are observed [ 15 , 16 , 17 ]. The increase in this B cell subpopulation in PRS might, therefore, represents an appropriate response to therapy, but further analyses should be performed in larger cohorts to draw the right conclusions.…”
Section: Discussionmentioning
confidence: 99%